The correspondence of Lord Acton and Richard Simpson, Volume 1 - Acton, John Emerich Edward Dalberg 1834-1902 (Cambridge University Press, 1971)
Lord Acton (1834–1902) and Richard Simpson (1820–76) were the principal figures in the Liberal Catholic movement of nineteenth-century England, an ultimately unsuccessful effort to reconcile the Roman Catholic Church with the leading secular thought of the day. They collaborated in editing the Rambler (1858–62) and the Home and Foreign Review (1862–4), two of the most distinguished Catholic periodicals of the period. The correspondence is the record of this collaboration and sheds light on the religious, political and intellectual history of mid-nineteenth-century England. Though heaviest for the years of their joint work on the Rambler and the Home and Foreign Review, the correspondence continued up to 1875, a year before Simpson's death
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Acton, John Emerich Edward Dalberg Acton / Baron / 1834-1902; Simpson, Richard / 1820-1876